Civil procedure : with Limitation Act, 1963 and chapter on commercial courts - Thakker, C. K (Takwani) (Eastern Book Company, 2017)
Procedural laws prescribe the method for enforcing rights and duties. The Code of Civil Procedure, 1908 gives the law relating to the procedure of the courts of civil judicature.